Methodological aspects of building the indicator for revealing distortions in company results - M. Yu. Savelyeva; S. A. Dudin; A. V. Trenixina (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Today it is extremely timely and acute to stir up academic quarters in order to develop methodological basis for assessing the degree of accounts trustworthiness in the interest of all groups of company stakeholders. The article studies theoretical and methodological aspects of assessing accounts manipulation. The author came to the conclusion about availability of shortcomings in the effective tools of assessing accounts manipulation, which are connected with determinism of indicators included in their structure and ignoring specificity of different types of company activity. The article proposes a new approach to probabilistic assessment of distortions in company accounts, which leans on mathematic-statistic models, namely typologization and multi-criteria estimation. This approach makes it feasible not only to find facts of accounts distortion but to identify their trend in the direction of overstating or understating. On the basis of this approach the integral indicator of assessing possibility of finance results’ distortion in company accounting in the direction of their overstating was built. It is connected with companies, whose principle type of activity is food production. The author draws a conclusion that more than a half of joint stock companies in the Russian Federation dealing with food production provide untruthful finance accounting (with the possibility of over 60%), which overstates finance results of its work.